KETIDAKBERLANJUTAN DALAM KONSUMERISME PARIWISATA: SEBUAH TINJAUAN KRITIS - Ray March Syahadat; Hendrie Adji Kusworo (UHN IGB Sugriwa Denpasar, 2022)
The success of the tourism industry is more quantitatively measured so it tends to ignore values that are not visible in it. Some consumerism developments in tourism even though they are financially profitable, it can actually losses if they fail to identify the sources of the leakage. This article is a critical review that aims to provide insight into the topic of unsustainability in tourism consumerism. Based on the results of the analysis, the unsustainability can be seen from the decline in environmental quality, economic waste and leakage, as well as social changes